Pengaruh umur bulan terhadap hasil tangkapan dengan jaring insang hanyut (Soma Landra) (Effect of moon phase on catches of drift gill net (Soma Landra)) - Ditsen Pangauan; Lefrand Manoppo; Mariana Elizabeth Kayadoe; Lusia Manu (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2020)
Soma landra is classified as drift gillnet which rectangular shaped and it equipped withÂ  floats, head rope, buoy rope, towing rope and sign buoy. In operation, it is installed in a position to cut the current direction with the intention of blocking the fish motion. The influence of moon phase is one of the factors that is closely related to fish behavior, where one of them is interested in light. Besides the brightness of the moonlight can be affected to the efficiency of capture. Therefore, the aims of this study were determined the effect of moon phase on catches and determined the catches at each moon phase. Randomized Block Design (RBD) was used in this study. The analyzed indicated that difference or reject Ho, means there are differences in catches in each moon phase. The species of fish caught is flying fish in the local language known as Marluga (Cypsilirusolegoleptis) as a target fishes with a total catch of 364.On the full moon as many as 106 (29.12%), the final perennial of 57 (15.66%), the dark moon of 79 (21.70%) and the initial peraniage of 122 fishes (33.52%).